A Comparison between the Politics of Conservatism and Reformism in the Islamic Republic of Iran - Karim Ghasemi (سپهر سیاست, 2020)
The purpose of the present study is to compare the policies of two political approaches in the Islamic Republic of Iran known as conservatism and reformism. To this aim, using the descriptive-historical method and Laclau and Mouffe’s discourse theory as the theoretical framework of the study, it was attempted to comparatively delve deep into the policies of conservatism and reformism in Iran. The results indicate that the identities and competitions in the intellectual framework of conservatism rely upon a fundamental concept known as “Willayat” (guardianship) so under the influence of this perception, they believe in the legitimacy of the establishment and a rather conservative political system. However, in the intellectual system of reformism, “people” have a central role as the reformists believe in the legitimacy of people and an open political system. Each of the above approaches attempt to have hegemony in the political realm, highlight their meaningful system, deconstruct, and marginalize their rival.